Analyses of the Photospheric Magnetic Dynamics in Solar Active Region 11117 Using an Advanced CESE-MHD Model - Jiang, Chaowei; Wu, Shi T.; Feng, Xueshang (Frontiers in Astronomy and Space Sciences, 2016)
In this study, the photospheric vector magnetograms obtained by Helioseismic and Magnetic Imager on-board the Solar Dynamics Observatory are used as boundary conditions for a CESE-MHD model to investigate some photosphere characteristics around the time of a confined flare in solar active region NOAA AR 11117. We report our attempt of characterizing a more realistic solar atmosphere by including a plasma with temperature stratified from the photosphere to the corona in the CESE-MHD model. The resulted photospheric transverse flow is comparable to the apparent movements of the magnetic flux features that demonstrates shearing and rotations. We calculated the relevant parameters such as the magnetic energy flux and helicity flux, and with analysis of these parameters, we find that magnetic non-potentiality is transported across the photosphere into the corona in the simulated time interval, which might provide a favorable condition for producing the flare.